Best management practice adoption amongst potato producers in Ontario: a study of drivers and barriers - Potter, Charlotte; Sarapura-Escobar, Silvia; VanderZaag, Peter; Salari, Danial; Zink, Regan (Frontiers in Sustainable Food Systems, 2024)
Best management practices (BMPs) are defined by OMAFRA as practical, affordable alternatives to conventional production systems, which improve agricultural production systems’ ability to address social, economic and ecological challenges. BMPs enhance the viability and sustainability of agriculture when successfully applied, but in systems where intensive industrial agriculture predominates their use is limited. Working with diverse potato producers in South-Western and Central Ontario, this project applied a Systems Thinking approach to understand motivating drivers and structural, institutional and organizational barriers impacting the adoption of BMPs for potato cultivation. Using a mixed-methods approach, this study collected quantitative and qualitative data using a farm-level survey, focus groups, workshops, and participant observation. Data was collected regarding demographics, management approaches, social networking and perceived challenges with BMP uptake. Analysis of our data revealed that family and future generations, ecosystem, soil and human health, community and social relationships, and efficiency and profitability were motivating drivers (based on beliefs and values) influencing management decisions. However, structural, institutional and organizational barriers (including market access, regulation, production efficiencies and competition), mediate producers’ abilities to act according to these motivations. Small-scale, medium-scale and large-scale producers are impacted by these barriers differently. In understanding the decision-making factors which drive BMP uptake in Ontario’s potato sector, policy and program design can leverage drivers and reduce barriers.